2004
DOI: 10.1007/s00784-004-0267-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo validation of the historical in vitro thermocycling temperature range for dental materials testing

Abstract: In dental research, restorative materials have been regularly subjected to alternating in vitro thermal stress in investigations since the 1950s, in order to simulate in vivo alternating temperature stress and to artificially stress them in vitro. The provocation temperature is mostly 5 degrees C for cold provocation, and 55 degrees C for hot provocation. These temperatures are determined quite arbitrarily based on very few examinations in vivo. Extensive temperature data for the approximal space of teeth, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 31 publications
0
43
0
2
Order By: Relevance
“…[20][21]32 Thermocycling may still be considered a valuable means to stress the adhesive interface. 19 It must be noted, however, that the influence of thermocycling on bond strength may depend on the specific test set-up or adhesive used. 20,32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21]32 Thermocycling may still be considered a valuable means to stress the adhesive interface. 19 It must be noted, however, that the influence of thermocycling on bond strength may depend on the specific test set-up or adhesive used. 20,32 …”
Section: Discussionmentioning
confidence: 99%
“…Thermocycling is a widely accepted artificial mode of aging used to simulate alternating in vivo temperatures. 19 Although thermocycling does not always influence the mechanical properties of resin composite materials, it may result in the decreased bonding of resin composite to enamel 20 or dentin, particularly when increasing the number of cycles. 21 Since the curing rate and curing mode may affect the polymer structure, [22][23][24] thermocycling may have an influence on shear bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…2b). All specimens were stored in distilled water for 24 h at 37 • C, followed by thermocycling (5000 cycles at 5 • C and 55 • C, with a 30 s dwelling time in each bath and 2 s of transferring time) [23].…”
Section: Bonding Proceduresmentioning
confidence: 99%
“…Corrosion, the graded degradation of materials by electrochemical attack, is of concern particularly when orthodontic appliances are placed in the hostile electrolytic environment provided by the human mouth [36]. Investigators have shown that thermocycling regimen comprising a minimum of 500 cycles in water between 5 and 55°C is an appropriate artificial aging test [26,35]. The results of the current study revealed that thermocycling has a significant effect on the release of Ni from orthodontic appliances.…”
Section: Discussionmentioning
confidence: 67%
“…Thermocycling process has been introduced as an artificial aging methodology [35], which is utilized for evaluating the influence of thermal stresses on dental materials. Orthodontic appliances are subject to larger temperature variations than most other parts, coping with ice-cold temperatures (0°C) through to hot coffee and soup (60°C).…”
Section: Discussionmentioning
confidence: 99%